Perancangan Sistem Informasi Jasa Penjualan Barang Berbasis Web Untuk Civitas Akademika Perguruan Tinggi di Kota Padang - Fadhli Ranuharja; Oktoria Oktoria; Nurindah Dwiyani (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
The purpose of this final taskto designan information system web-based serviceforthe sale of goodsforCollegeacademic communityin Padangcity.Salesserviceinformationsystemis awholesystemofactivitiesindicatedfor planning, pricing, promotinganddistributinggoods, services, ideasto the target marketin order toachieve organizational goals. Informationsystemsgeneratemarkettingserviceswebsiteservicesfor thesale of goodsacademic communityin Padangcity. Information system designservicesisthe saleof goods, carried outbyusing theprogramminglanguageJava EnterpriseEdition(JEE) and aMySQL database. Toprovidesecurity(security) to the dataandinformation, thenusethe session.Keywords: Sales InformationSystems, JavaEnterpriseEdition(JEE), MySQLandSession.